How to Use "Publish or Perish" to Raise the Standard of Scientific Writing at State Administration Study Programme students, Sultan Syarif Kasim Riau State Islamic University - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This activity aims to improve the ability of State Administration Study Programme students at Sultan Syarif Kasim Riau State Islamic University to make scientific papers. A common problem found is the difficulty of obtaining relevant theory in research. This has had an impact on the use of statutory products as a research theory, so much so that it affects the quality of the scientific papers produced. To overcome these problems, mentoring activities are carried out using the Publish or Perish application. Through the use of this application, participants will easily obtain a large number of scientific articles in a very short time. The scientific article can be used as a research theory. Prior to this activity, none of the participants knew about this application. Based on the results of the evaluation, after this activity, the participants will know the functions and all the features contained in this application. In addition, participants have also been able to install this application independently and use it properly. Thus, it can be concluded that this activity has succeeded in increasing the ability of participants to write scientific papers.